Vibrating roller with compacted soil interaction modelling - I. S. Tyuremnov; D. A. Shorohov (Вестник СибАДИ)
Introduction. Vibrating rollers are the most common means of compacting soils in construction. The nature of stress development on the contact surface of the roller with the ground depends on the technical characteristics of the vibrating roller (the mass of the roller, the mass of the roller frame, the frequency and driving force of vibrations, the number and characteristics of the roller shock absorbers) and the properties of the soil.Materials and methods. Simulation of the interaction of a vibrating roller with compacted soil was carried out using a three-mass rheological model of the frame-roller-soil system. Differential equations of mass motion in contact and separation modes were solved numerically. To determine the numerical values of the loading time (increase in contact stresses from zero to the maximum value) and the unloading time (decrease in contact stresses from the maximum value to zero), as well as the maximum reaction force of the soil, a computational experiment was conducted on a rheological model. The mass of the vibrating roller module (the mass of the front axle) and the relative driving force were used as independent parameters of the vibrating roller. The coefficients of elastic and viscous resistance of the soil were chosen as independent parameters of the soil. The total number of combinations of factors was 192. The values of the time of loading and unloading of the soil, as well as the maximum strength of the soil reaction, were determined by oscillograms of changes in the strength of the soil reaction over time.Results. Using the STATISTICA program, regression equations, to calculate the numerical values of the loading and unloading time of the soil, as well as the maximum reaction force of the soil and the corresponding values of the reliability coefficients of the multiple approximation, were obtained.Discussion and conclusion. The rheological model reproduces the asymmetric nature of changes in contact stresses during soil compaction by a vibrating roller, observed in experimental stress oscillograms obtained during field experimental studies. The results obtained are important for calculating the depth of stress propagation in the ground and the distribution of stresses in the ground after the passage of a vibrating roller using a wave approach to describing stress propagation in the ground. In the future, it is advisable to conduct a computational experiment with an expanded list of independent parameters of the roller, including the oscillation frequency.